Economic impact of the Magical Towns from the perspective of citizens: Izamal, Yucatán (GEON Journal (Management, Organizations and Business), 2021)
Since 2002, following its designation as a Magical Town by the Ministry of Tourism, the municipality of Izamal has experienced a significant dynamism. This led to an economic transition of the municipality, which has had an impact on the economy and on the activities carried out by the citizens, which have been scarcely addressed for the implementation of actions that have an impact on the economic growth of the region.The purpose of this study is to identify the economic impact of the Magical Town distinction from the citizens' perspective.A descriptive quantitative method was used for this article, taking into account a 95% confidence level for the calculation of the sample size, regarding the instruments collected; an estimation error of 0.051, with a sample proportion in favor (p) and against (q) of 0.5, respectively.First of all, the population has shifted from traditional economic activities to providing services, heading towards tourism. In the same way, an improvement in the buildings' physical infrastructure was observed in the downtown area of the locality, the immersed economy played a fundamental role with the participation of the businessmen, merchants and mainly of the population (citizens) as a whole; therefore, the tourist affluence represents susceptible economic benefits for the population's economy.In 2021, it was identified that the handicraft commerce does not have a significant increase in relation to 2019, contrary to the commerce of typical clothing and food services, as products directed towards tourism, which allows the improvement of citizens' income.To conclude, it can be mentioned that dissemination is a fundamental element to promote the actions directed towards the Magical Towns Program's citizens, which leads to tangible results for them.It contributes to the formulation of proposals directed to improve the perception of the program and the involvement of citizens in it.
Keywords: Citizenship; Economic Dynamics; Economy; Population; Services; Tourism; Z320 Tourism and development; D62 Welfare economics